Successful Compilation of the Regional Government Implementation Report (LPPD) in Kepahiang Regency in 2024 - Putri, Yollanda Arsyati; Suharto, Sugeng; Ramadhan, Adityo Pratikno (Empiricism Journal, 2026)
The preparation of the Regional Government Implementation Report (LPPD) is a mandatory obligation of local governments as a form of accountability to the central government for the implementation of regional autonomy and governance during one fiscal year, while also functioning as an instrument for performance evaluation, transparency, accountability, and development planning. However, studies on LPPD have generally emphasized regulatory compliance and administrative procedures, with limited attention to how leadership, coordination, staff competence, and digital systems interact in shaping reporting success at the local level. This study aims to analyze the success of the 2024 Kepahiang Regency LPPD preparation based on timeliness of submission, completeness of data, accuracy of performance indicators, coordination among Regional Apparatus Organizations (OPDs), and compliance with technical guidelines. The Research employed a qualitative descriptive approach using interviews, observations, and documentation review of LPPD-related records. The findings show that the 2024 Kepahiang Regency LPPD was submitted on schedule, supported by complete data contributions from relevant OPDs and the use of the SILPPD digital reporting system. Regular coordination meetings, leadership monitoring, and the experience of reporting staff were identified as important factors supporting timely and accurate preparation. Nevertheless, several practical challenges remained, including differences in data interpretation among OPDs, uneven technical capacity, and the need for continuous adaptation to system updates. These findings indicate that successful LPPD preparation should not be viewed merely as procedural compliance, but as the result of interaction between organizational leadership, institutional collaboration, administrative competence, and digital governance support. This study contributes to the literature by offering an integrated perspective on LPPD success and by distinguishing between administrative success, reflected in timeliness and completeness, and substantive success, reflected in the use of reports for governance improvement, policy learning, and better public service management outcomes.